(untitled) (Research, Society and Development, 2021)
The national policy of attention to men’s health aims to integrate the male population to health services, as this target audience does not often seek medical attention due to cultural aspects, shame or lack of time. Thus, we have as a problem the high male mortality. The present study has the general objective of analyzing the epidemiological profile of male mortality, and, as an objective, to specify and identify the causes of mortality among men, in addition to describing the socio-demographic profile of the age group, color / race, education and macroregions. This work is a descriptive, retrospective study, with a quantitative approach. The research was carried out with data made available in the DATASUS system in which the main causes of death in the male population between 2014 and 2018 were analyzed, in order to identify and analyze the major epidemiological causes of deaths in men. The results of the study show that between 2014 and 2018 there were 3,607,966 deaths in men. And that the southeast region had the highest percentage of deaths among the macro-regions with 44.11%. As for the age group 80 years or more with 21.76%. Regarding color / race, white predominated with 47.67%. The predominant level of education was 1 to 3 years 23.08%, ignored with 22.98%. The research may reinforce the data already obtained by other researchers, or, still, demonstrate other indices not yet surveyed. It concludes the greater frequency of male deaths from preventable causes, the importance of investments in health promotion and disease prevention in primary care is highlighted.